AVALIAÇÃO DOS EFEITOS DO EXTRATO HIDROALCOÓLICO DAS FOLHAS DE Syzygium cumini (L.) SKEELS SOBRE O PERFIL METABÓLICO E ESTADO REDOX DE RATOS COM DIABETES INDUZIDO POR DEXAMETASONA. - RIBEIRO, Nathalee Liberal Xavier (2017)
Oxidative stress has been associated to many chronic-degenerative pathologies, including type 2 diabetes mellitus. As it is an endemic disease, there is a constant search for new anti-diabetic drugs, as well as adjuvant treatments. In this context, the plant species Syzygium cumini (L.) Skeels stands out, popularly known as “jambolão” and traditionally used to control diabetes. Therefore, this study aims to assess the effects of the hydroalcoholic extract of the Syzygium cumini leaf (EHSc) on the metabolic profile and redox status of rats with dexamethasone-induced diabetes. Male Wistar rats were divided into three experimental groups: CTR - control group (NaCl 0.9%, vo), DEX - diabetic group induced with dexamethasone (1 mg / kg / day, ip) and EHSc - group treated with EHSc (500 mg / kg / day; vo). Animals were accompanied for 10 days, and the induction was performed from the 6th day, while EHSc treatment was performed over 10 days. Before diabetes dexamethasone-induction, CTR and DEX groups showed similar weight gain, and DEX + EHSc group, weight loss. After induction with dexamethasone, DEX and DEX + EHSc animals had marked weight loss. Retroperitoneal fat pad decreased by 41.3% in DEX and 34.2% in DEX + EHSc animals, as compared to the CTR, p <0.05. However, no statistically significant difference observed between relative weights from other organs evaluated. There was an increase in fasting glucose in the DEX group by 34.1%, in relation to the CTR group. Treatment with EHSc attenuated the hyperglycemic effect of dexamethasone, since the fasting glucose of the DEX + EHSc group has reduced. There was an increase of 142.5% of the serum triglyceride in DEX group in relation to CTR, p <0.05. EHSc treatment attenuated the hypertriglyceridemic effect by 34.4%, as compared to the CTR group, p <0.05. The serum insulin levels of DEX animals were about 10-fold higher than CTR ones, p <0.05. EHSc treatment improved insulinemia in DEX + EHSc group. Under basal conditions (glucose 5.6 mM), pancreatic islets of DEX and DEX + EHSc animals presented hypersecretion of insulin. However, under conditions of hyperglycemia (glucose 16.7 mM), islets from DEX + EHSc animals showed a reversal of dexamethasone-induced hypersecretion. Dexamethasone increased hepatic triglyceride content by 106.1% in comparison to CTR, whereas EHSc treatment totally prevented this accumulation. Serum activity of superoxide dismutase in DEX animals was around 3-fold higher than CTR, and there was a similar increase in DEX + EHSc group. Catalase activity enhanced in DEX animals, in relation to CTR, and it was reduced in the DEX + EHSc. The activity of glutathione peroxidase did not vary between groups. For determining oxidative damages due to oxidative stress, serum hydroperoxide formation was assessed and it revealed an increase of 27.2% of these products in serum of DEX animals, an effect not observed in DEX + EHSc. Our results corroborate the EHSc as a potential source of antioxidant compounds that improves responses to oxidative damage as well as insulin secretion and other metabolic parameters.